2022
DOI: 10.4269/ajtmh.22-0421
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcomes Associated with Mild COVID-19 Infection in an Obstetric Cohort in Brazil

Abstract: Previous coronavirus epidemics were associated with increased maternal morbidity, mortality, and adverse obstetric outcomes. Reports for SARS-CoV-2 indicate that the obstetric population is at increased risk for severe illness, although there are still limited data on mild COVID-19 infection during pregnancy. To determine the association between mild COVID-19 infection during pregnancy, and maternal and neonatal outcomes, we performed a prospective cohort study among pregnant women with COVID-19 and a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
7
0
1
Order By: Relevance
“…In this study, all SARS-CoV-2 infections occurred during the third trimester of pregnancy, with an average gestational age of 246.7 ± 21.56 days at the time of SARS-CoV-2 infection. These findings are consistent with other studies conducted during the same period ( Antoun et al, 2020 ; Kumari, Anand & Vidyarthi, 2022 ; Santos et al, 2022 ; Yan et al, 2020 ), highlighting the importance of continued prophylaxis throughout pregnancy. Approximately 15.6% of pregnant women with COVID-19 were diagnosed with gestational diabetes mellitus (GDM), compared to 10.4% in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, all SARS-CoV-2 infections occurred during the third trimester of pregnancy, with an average gestational age of 246.7 ± 21.56 days at the time of SARS-CoV-2 infection. These findings are consistent with other studies conducted during the same period ( Antoun et al, 2020 ; Kumari, Anand & Vidyarthi, 2022 ; Santos et al, 2022 ; Yan et al, 2020 ), highlighting the importance of continued prophylaxis throughout pregnancy. Approximately 15.6% of pregnant women with COVID-19 were diagnosed with gestational diabetes mellitus (GDM), compared to 10.4% in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…A small but important control-matched prospective cohort study in Brazil (n = 88) followed pregnant women after testing positive for COVID-19 (n = 84), finding that 75.9% developed LC (31). This study also found that patients given glucocorticoids to treat COVID-19 during pregnancy were at higher risk (RR 6.92, 95% CI 1.70-28.07) of persistent fatigue (31), a key and debilitating LC symptom.…”
Section: Long Covid and Pregnancymentioning
confidence: 73%
“…Second, we evaluated non-specific T cell responses during the acute and convalescent phases of COVID-19 without assessing SARS-CoV-2-specific T cell responses. Another important area for future study beyond the scope of the experiments performed here is to understand how maternal immune responses during acute SARS-CoV-2 infection and convalescence relate to longer-term immune function in individuals after pregnancy 118,120,122 (e.g., development of long COVID or other immune syndromes), and the short- and long-term health outcomes of their offspring. Members of our study team have examined both short-term neurodevelopmental 119,121 and cardiometabolic 123,124 outcomes in offspring of mothers infected with SARS-CoV-2 in pregnancy, demonstrating increased risk for neurodevelopmental diagnoses at 12 months particularly pronounced in male offspring, and increased risk for altered growth trajectories in the first year of life that may presage an increased risk for early-onset cardiometabolic complications.…”
Section: Discussionmentioning
confidence: 99%